Planned home birth as a safe alternative to hospital birth for low-risk women: a systematic review - Auwalu, Muhammed; Lee, Khuan; Md Said, Salmiah; Shariff-Ghazali, Sazlina; Ibrahim, Abdullahi Haruna (African - British Journals, 2023)
Home birth is a widely practised norm among women in most developing countries. Studies continue to evaluate the safety of planned home birth (PHB) for low-risk women in high-income countries. However, such studies are scarce in Africa and other developing countries. The study examined PHB as a safe alternative to planned hospital birth for low-risk women. An electronic search was carried out on databases such as Medline database, Cochrane, Google Scholar, PubMed, and CINAHL to identify studies published in English from January 2007 to December 2017. A Meta-analytic study, systematic reviews, and observational (prospective and retrospective) studies were included in the literature reviews. The studies were analyzed using descriptive and narrative synthesis. The strength and or limitations of each study were assessed. Sixteen eligible articles were finally reviewed. PHB is equally safe in terms of complication (especially postpartum haemorrhage) compared to planned hospital birth. PHB would have a similar outcome in reducing maternal death for low-risk women if compared with planned hospital birth. Although neonatal asphyxia is mixed across studies, PHB is associated with a similarly low rate of neonatal intensive care unit admission. It was also indicated that there was no increase in neonatal mortality for PHB, especially for parous women. PHB compared to the hospital is associated with a similar low risk of maternal complications, maternal deaths, newborn complications, and newborn deaths, especially for parous women. Therefore, PHB is a safe alternative to hospital birth for low-risk women. While studies that are more recent are required to evaluate its feasibility and safety in developing countries, PHB (if properly attended) may reduce maternal and newborn complications and death associated with unplanned home births.